Improving Students’ Speaking Skills Through Contextual Teaching and Learning Model of Students' 21st Century - Astuti, Tri Puji; Sudar, Sudar; Sukarni, Semi (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2025)
This classroom action research aimed to improve the speaking ability of first-year students at SMP Negeri 1 Kebumen through the Contextual Teaching and Learning (CTL) model, targeting the enhancement of student’s 21st century skills. The study was conducted in class VII A, involving 30 students as the sample. The research was implemented in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using both qualitative and quantitative methods, including speaking tests, observation sheets, and student interviews. The instruments employed for data collection were validated for reliability and consistency. The implementation of the Contextual Teaching and Learning (CTL) model can significantly improve students’ speaking skill as well as foster their 21st century skills, such as engagement, critical thinking, and communication. The results indicated a significant improvement in the students' speaking skill, as evidenced by the increased mean scores from the pre-test to the post-test in both cycles. Additionally, the students demonstrated enhanced engagement, critical thinking, and communication skills. Findings confirm that the CTL model is effective in improving student’s speaking skill and simultaneously strengthening their 21st century skills. Therefore, the CTL model can be recommended as a valuable strategy for enhancing both linguistic proficiency and essential competencies in junior high school students.